REALITAS LITERASI MEDIA PADA IBU-IBU JAMAAH MAJELIS TAKLIM NURUL HIKMAH, DESA TANJUNG KARANG, CIGALONTANG, TASIKMALAYA, JAWA BARAT: REALITAS LITERASI MEDIA PADA IBU-IBU JAMAAH MAJELIS TAKLIM NURUL HIKMAH, DESA TANJUNG KARANG, CIGALONTANG, TASIKMALAYA, JAWA BARAT - Santa Lorita Simamora (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2021)
Impressions program broadcast media were more varied, especially the entertainment program demanding society audience should have the ability to screen a wide range of entertainment programs such content. The reality is not so, is not proportional between variety program and the community's ability to filter information which may enter into her mind. This is especially seen in public audiences in rural areas. As stated by Nielsen Media Research that the majority of the audience in Indonesia is a community social economic status C and D, where their ability to seek more entertainment through a private television station. While their ability to sort out the entertainment program content can not be said to be feasible. The Research method used is descriptive qualitative research. Through this research, the researcher tries photographing reality lack the ability of mothers touched Majelis Taklim Nurul Hikmah, Tanjung Karang Village, Cigalontang, Tasikmalaya, West Java during the first month, which is the period of May 29 to June 26, 2018. Additionally depth interviews were conducted that research subjects 30 mothers touched Majelis Taklim Nurul Hikmah. The results of the research findings that the ability of mothers in sorting, filtering content impressions entertainment program is minimal, so with various limitations, the mothers can not provide assistance to the children or their grandchildren when watching television programs, especially the entertainment program.